DETEKSI AREA KERUSAKAN PADA CITRA TERUMBU KARANG AKIBAT CORAL BLEACHING BERBASIS PENGOLAHAN CITRA DIGITAL - Mutmainnah Muchtar; Riska Riska (LPPM Unbaja, 2023)
Coral reefs have a very large role in marine ecosystems, because they provide rich habitats and support biodiversity. Segmentation on images of coral reefs experiencing coral bleaching is also very important. Coral bleaching is a phenomenon in which coral reefs lose their symbiotic algae pigments, resulting in bleaching and possibly death of coral reefs. By segmenting coral reef images that experience coral bleaching, we can separate areas affected by bleaching from areas that are still healthy. This study aims to detect areas of damage that occur in underwater images of coral reefs that have experienced coral bleaching. By using techniques in digital image processing and segmentation based on colour intensity, satisfactory results are obtained. The test results show that the RAE and ME values are quite low, namely 0.051 and 0.035 respectively with an average processing time of 0.2 seconds. This research is expected to assist in further analysis and modelling related to coral bleaching to understand the causative factors and develop appropriate protection strategies.